Prevalence and therapeutic implications of chronic kidney disease in heart failure - Hwei Sung, Ling (Elsevier, 2023)
Introduction Heart failure (HF) is common and is associated with poor prognosis. Chronic kidney disease (CKD) is common in HF, and shares many risk factors with HF such as age, hypertension, diabetes, and coronary artery disease. Objective To review the prevalence of CKD in HF and the therapeutic implications. Method Patients with HF with reduced ejection fraction (HFrEF) in Sarawak General Hospital HF clinic were analyzed retrospectively. CKD was diagnosed by reduced estimated glomerular filtration rate (GFR) according to 2021 CKD-EPI equation. Report We have evaluated 55 patients. Their mean age are 57 and are predominantly male (62%). 42% of our patients have CKD. The prevalence of stage 3, 4 and 5 CKD was 27.3%, 7.3% and 7.3% respectively. At 3 months, ACEi/ARNI prescription in CKD patients was significantly lower 65% compared to non-CKD patients 97% (p = 0.002). MRA prescription was also significantly lower in CKD group 43% compare to 75% (p = 0.018). There was no different in BB and SLGT2i prescriptions. HF hospitalization rate were no Conclusion CKD prevalence is high in our HF patients. It affects optimization of the GDMT, however there was no difference in terms of clinical outcome.